Agricultural law as an instrument for agricultural and rural development - Mugarra, Miriam Velazco (Przegląd Prawa Rolnego, 2018)
The aim of the article was to present the contemporary challenges of agricultural law in relation to sustainable development of rural areas, taking into account agricultural policies implemented at the local, regional, international and global level. In particular, the article focuses on the impact of the territorial approach on sustainable development of rural areas and its importance for the agricultural law. The implementation of the concept of sustainable agriculture in Cuba requires consistent implementation of the technological progress as well as a certain moderate, rational and economically justified intensification of production followed by a reduction in the degradation of soil production potential. It is also necessary to develop and modernise the technical infrastructure of rural areas and of the farms themselves. These activities must aim at increasing the level of education and expertise among farmers and their environmental awareness, and they require financial support from the state budget and regional funds. It is also necessary to improve the revenue-related situation of agriculture, as it determines the possibilities of investment and pro-ecological activity, and in consequence ensures the food security of the country. According to the author, the territorial approach is an effective instrument facilitating public management of rural areas and contributing to the further socio-economic development of the rural population.